2014
DOI: 10.3109/10826084.2014.880485
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions of Peer Pill-Popping: The Prevalence, Correlates, and Effects of Inaccurate Assumptions About Peer Pharmaceutical Misuse

Abstract: Peer behaviors may significantly influence personal behavior yet individuals may not accurately estimate their peers' actions. Overestimations of peer substance use may encourage initiation or exacerbate extant problems. The present study examines misperceptions of peer pharmaceutical misuse and explores the relationship between reported misuse and perceptions of misuse for four categories of prescription drugs. Data collected from 2,349 college students in the Southeastern United States were analyzed and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
4
10
0
1
Order By: Relevance
“…The only study that examined perceptions with respect to prescription sedatives by Sanders and colleagues (2014) found that 65.7% of students perceived the recreational use of prescription sedatives to be the norm among their peers despite only 2.6% of the sample reporting recreational use of these substances during the last month. More than a third of participants overestimated (26.3%) or extremely overestimated (10.2%) their peers' use, and recreational users of prescription sedatives were more likely to overestimate their peers' use of these substances (Sanders, et al, 2014). These findings are in line with our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The only study that examined perceptions with respect to prescription sedatives by Sanders and colleagues (2014) found that 65.7% of students perceived the recreational use of prescription sedatives to be the norm among their peers despite only 2.6% of the sample reporting recreational use of these substances during the last month. More than a third of participants overestimated (26.3%) or extremely overestimated (10.2%) their peers' use, and recreational users of prescription sedatives were more likely to overestimate their peers' use of these substances (Sanders, et al, 2014). These findings are in line with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have examined misperceptions or self-other discrepancies about the non-medical use of prescription drugs, as well as associations between descriptive norms and personal use, particularly regarding prescription stimulants (Helmer, et al, 2016;Kilmer, Geisner, Gasser, & Lindgren, 2015;McCabe, 2008;Sanders, Stogner, Seibert, & Miller, 2014;Silvestri & Correia, 2016), with only one study, to date, investigating prescription sedative use (Sanders, et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Peer factors associated with adolescent NMPDU include exposure to drug use and pro-drug attitudes (Ford, 2008a; Ford and Hill, 2012). However, other peer factors largely overlooked in studies of NMPDU include receiving substance offers (Ellickson et al, 2004; Siegel et al, 2015) and overestimating peer use (D'Amico and McCarthy, 2006; Ober et al, 2013; Wu et al, 2015), although the prevalence of NMPDU overestimation has been documented (McCabe, 2008; Sanders et al, 2014). Family factors relevant to NMPDU include poor parental monitoring and involvement (Ford, 2009; Ford and McCutcheon, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the importance of social approval among adolescents (Pechmann, et al, 2003), one area where social marketing may be successfully employed is in correcting the likely misperceptions about the prevalence of AS use among peers (Sanders, Stogner, Seibert & Miller, 2014). Relationship between reasons to use and intervention messages.…”
Section: Gaps In the Doping Literaturementioning
confidence: 99%